STRUCTURAL DESIGN OF MIXED-USED BUILDING GREEN RIBBON IN MANGGARAI, JAKARTA SELATAN - Alim Wijaya, Eka
Green Ribbon is a multifunctional building designed to meet residential needs, shopping centers, and entertainment centers integrated in an individual building block. This Final Project includes designing buildings from structural engineering aspects. The design consists of determining the structural system, calculating gravity loading on the structure, calculating earthquake effect as equivalent lateral loading, structural modeling, evaluating earthquake resistance of the structural system, design and detailing of structural elements. The structural system used for the Green Ribbon is dual system with special moment bearing frames and special structural walls. Service load that works on a structure has a different value based on the function of the room, starting from the corridor to the apartment room. The earthquake load for the structure is relatively large, so the structure must be designed for class-D seismic design category. Structural modeling is modelled with ETABS, and is done with a two-stage analysis method. The purpose is to make design easier, because the building consist of two different part. The upper structure has high and slender characteristics, while the lower structure tends to be wide, relatively short, and stiff. After modelling phase, the structural system must be evaluated in order to fulfill the requirements in the SNI 1726 2012. Indeed, in order to fully meet the requirements of the codes, it is necessary to do countless iterations of changing structural configuration, especially if the structure is not symmetrical, or has other irregularities. The structural analysis then can be done automatically with the help of ETABS software. The design of structural elements is then worked based on the style that has been obtained from the structure analysis process. The design of the structure must meet the requirements in SNI2847:2013 as the codes for design and detailing of reinforced concrete in Indonesia. Also, earthquake resistant structures must have technical specifications that are different from the usual structure, for example each stirrup reinforcement for earthquake resistant structures must be 135 degrees bent at one end, then a crossties must be provided at maximum every 350 mm for earthquake resistant compressive structural components.